2009
DOI: 10.1042/bst0370079
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the base excision repair (BER) complex in Pyrococcus furiosus

Abstract: We have been studying the functions of PCNA (proliferating-cell nuclear antigen) for the assembly and reassembly of the replisome during replication fork progression. We have identified the functional interactions between PCNA and several proteins involved in DNA replication and repair from Pyrococcus furiosus. We recently reported that the activity of UDG (uracil-DNA glycosylase) in P. furiosus (PfuUDG) is stimulated by PCNA (PfuPCNA) in vitro, and identified an atypical PCNA-binding site, AKTLF, in the PfuUD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Conversely, PfuPCNA was coprecipitated with PfuAPE by an anti-PfuAPE antibody. We previously showed that PfuUDG and PfuPCNA were coprecipitated with each antibody (46).
Figure 4.Physical interaction between PfuAPE and PfuPCNA.
…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, PfuPCNA was coprecipitated with PfuAPE by an anti-PfuAPE antibody. We previously showed that PfuUDG and PfuPCNA were coprecipitated with each antibody (46).
Figure 4.Physical interaction between PfuAPE and PfuPCNA.
…”
Section: Resultsmentioning
confidence: 99%
“…In addition, as complete genome sequences of three Pyrococcus species became available at a relatively early stage, members of the Thermococcales have been utilized to study a wide range of archaeal biology. These include DNA replication and repair (Hopkins & Paull, 2008;Williams et al, 2008;Yoshimochi et al, 2008;Kiyonari et al, 2009;Mayanagi et al, 2009;Nishida et al, 2009), transcription and its regulation (Vierke et al, 2003;Lee et al, 2005Lee et al, , 2007Goede et al, 2006;Kanai et al, 2007;Santangelo et al, 2007;Hirata et al, 2008a), carbon and energy metabolism (Sapra et al, 2003;Verhees et al, 2003;Siebers & Schönheit, 2005), CRISPR systems (Hale et al, 2009), and cellular responses to stress, such as oxidative (Jenney et al, 1999;Clay et al, 2003), osmotic (Neves et al, 2005;Rodrigues et al, 2007), and temperature stress (Laksanalamai & Robb, 2004;Danno et al, 2008;Fujiwara et al, 2008;Kanzaki et al, 2008;Kida et al, 2008). The abundant genome sequences have also promoted a wealth of '-omics' research including transcriptomics Lee et al, 2006;Trauger et al, 2008), proteomics , structural genomics (Hura et al, 2009), and other genome-based high-throughput strategies (Keese et al, 2010).…”
Section: Why Study Thermococcales?mentioning
confidence: 99%
“…4 Base excision repair is present in every living organism, even in archaea. 5 A third line of defense exists in this particular kingdom, embedded in the DNA polymerase itself and in the progression of the replication fork. Indeed, archaeal family B DNA polymerases possess an N-terminal domain that can recognize and bind deaminated bases 4 nt upstream the primer-template (P/T) junction during DNA replication.…”
Section: Introductionmentioning
confidence: 99%